Self-reported exercise behaviour and perception of its importance to recreational divers - Kovacs, C.; Buzzacott, Peter (Wydawnictwo Via Medica, 2017)
© 2017 PSMTTM. Background: This study examined self-reported physical activity and perceptions of exercise importance among certified divers in two distinct age groups. Materials and methods: Questionnaires were distributed by hand at dive sites in three states of the United States, half to students from an academic programme in scuba diving at a regional university. The survey included questions about health status, dive history, certification levels, structured exercise activity levels and perceived importance of regular exercise to their health, diving ability, and safety. Also included was the Godin-Shephard Leisure-Time Physical Activity Questionnaire, a validated physical activity classification instrument for use among adults. Results: Non-students were older than the students and had greater diving experience. There was no detectable difference between groups in perceived exercise importance to health (p = 0.69), diving ability (p = 0.75), or diving safety (p = 0.25). Fitting age, sex, occupation and number of dives to a generalised linear model to predict Godin-Shephard scores, number of dives was removed first (p = 0.43), followed by student status (p = 0.33). Remaining predictors of Godin-Shephard exercise scores were age (-0.004 per year, p < 0.0001) and sex (males = + 0.11, 95% CI 0.04-0.17, p = 0.0012). Both groups reported similar structured exercise regularity, overall health and perceived importance of regular exercise for health, diving and safety. Conclusions: Despite acknowledging the importance of exercise, Godin-Shephard scores for physical activity decrease with age.